Sugarcane hybrids with original low lignin contents and high field productivity are useful to reach high glucose yields from bagasse. (April 2015) - Laurito-Friend, D.F.; Mendes, F.M.; Reinoso, F.M.; Ferraz, A.; Milagres, A.M.F.
Abstract: Five sugarcane hybrids plus a reference material were evaluated according to the glucose yields obtained after alkaline-sulfite pretreatment and enzymatic hydrolysis. Sugarcane hybrids with varied original chemical compositions were used to assess how contrasting samples might influence the integrated pretreatment and hydrolysis process. The hydrolysis efficiency of six samples treated at three different chemical loads, suggested that lignin and hemicellulose removals during the pretreatment were not the single factor necessary to reach high cellulose conversion levels in the enzymatic hydrolysis step. Pretreated samples with the highest total acid contents (mainly sulfonic acids) were also the most digestible materials. The glucose yields were heavily dependent not only on the digestibility of the pretreated materials but also on the field productivity of the plants. One of the hybrids, presenting high glucan yields after pretreatment and high digestibility, produced low glucose yields because it presented very low biomass productivity. In contrast, one of the hybrids that presented low glucan yield after pretreatment, but was highly digestible and presented high biomass productivity, provided the highest glucose yields in the data set, producing 4192 and 5629 kg of glucose per hectare after enzymatic hydrolysis for 24 h and 72 h, respectively. Highlights: Sucarcane with less lignin needs lower chemicals to reach high cellulose conversion. Lignin removals are not the single factor to reach high enzymatic conversion. Sulfonation has positive effect in the efficiency of enzymatic hydrolysis. Glucose yields depend on the digestibility of the materials and field productivity.